ENCOURAGING ENTREPRENEURIAL BEHAVIOR AND SPIRIT IN REALIZING ENTREPRENEURIAL INDEPENDENCE - Iwan Usma Wardani; I Wayan Lasmawan; I Nengah Suastika (Jurnal Ekonomi, 2022)
Attitude and behavior are the unity of a person's character formed by daily habits. An entrepreneur's behavior is influenced by internal and external factors. These factors are: (ownership, public relations), skills/competencies (competencies/skills), and incentives, external factors include the environment, so that attitudes and behaviors can be changed by oneself, and/or there is environmental pressure/influence Involves influences both inside and outside the environment that develop certain individual attitudes and behaviors. It is necessary to anticipate the difficulties faced by SMEs related to entrepreneurial assessment, business values ​​, and entrepreneurial behavior that can affect the realization of self-reliance efforts. This study analyzes the impact of entrepreneurship and entrepreneurial values ​​on entrepreneurial behavior to create entrepreneurial independence. This entrepreneurial spirit has a direct positive effect on entrepreneurial behavior and an indirect positive effect on entrepreneurial independence.